Preserving Evidence Integrity: Assessing Chain of Custody Issues in Tagaytay City Criminal Cases - Lumyaen D. Lidawan; Elizabeth Buena-Villa; Julius Guiller G. Luis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study explores the challenges faced by investigators in Tagaytay City, Cavite, in maintaining evidence integrity through the chain of custody. Conducted in 2025, it employed a qualitative descriptive design using structured interviews with purposively selected investigators at the Tagaytay City Satellite PNP SOCO Forensic Office. Data were analyzed through thematic analysis to uncover recurring issues in evidence handling. Findings revealed multiple challenges, including inconsistencies in investigator training, inadequate resources, and deficiencies in documentation practices. Many investigators demonstrated limited understanding of chain of custody protocols, resulting in procedural errors that compromise evidence reliability in court. Environmental factors such as extreme weather conditions and insufficient storage facilities further complicated the preservation of sensitive materials. Weak inter-agency collaboration, stemming from unclear communication and undefined roles, also hindered effective joint investigations. The study recommends tailored training programs on digital evidence handling and environmental preservation techniques to strengthen investigator competency, adoption of digital documentation systems to minimize human error, and establishment of clear inter-agency protocols. Upgrading evidence storage facilities and securing supplemental funding through public–private partnerships are also proposed to resolve resource constraints. It underscores the need for systematic improvements in evidence handling practices to safeguard justice. By addressing identified challenges and adopting the recommended strategies, law enforcement agencies in Tagaytay City can enhance operational efficiency and ensure that evidence is preserved and presented with the highest integrity. The study contributes valuable insights into the critical role of effective chain of custody management within the Philippine criminal justice system.